Input voltage/current distortion in switchmode power supplies, active and passive filtering, their costs and benefits - Gao, Xian (2016)
Since the past few decades, switch mode power supplies SMPS have been widely applied in many electronics and electrical engineering, bio-medical, military and other fields. As SMPS provides a wide range of effective features in converting power with low losses. It demonstrated great power efficiency, it can be as high as 90% with good design, enable to operate more than one input and over a wide range of input power supply.